Water pollution status of Deli River Medan, North Sumatra, based on Pollution Index (IP) and CCME WQI - Jamal, Aulia Fitri; Damar, Ario; Hariyadi, Sigid (Depik Jurnal Ilmu Ilmu Perairan, Pesisir, dan Perikanan, 2025)
Deli River has been designated as a national river that has made a major contribution to the economic growth and development in the Medan city of North Sumatra. However, rapid urbanization and human population growth have caused degradation of the quality of Deli River due to increasing pollution. This study aims to analyze the level of pollution of the Deli River using the Pollution Index (PI) and CCME Water Quality Index (WQI) methods with reference to Government Regulation Number 22 of 2021. The research location was divided into 4 stations from upstream to downstream of the Deli River. Based on PI method, stations 1, 2, and 3 were classified as lightly polluted, while station 4 experienced moderate pollution. The results were different when using the CCME WQI method, which showed that stations 1, 2, and 3 were classified as having fairly good waters, while station 4 was poor waters. Water quality analysis was carried out on 13 parameters, 5 of which exceeded the river water quality standard threshold, namely BOD, ammonia, Pb, Zn, and Cd.Keywords:Deli riverRiver pollutionWater qualityPollution Index (IP)CCME WQI